Single Virus Targeting Multiple Organs: What We Know and Where We Are Heading? - Prasad, Ashish; Prasad, Manoj (Frontiers in Medicine, 2020)
COVID-19 caused by SARS-CoV-2 has already infected more than 6. 3 million people worldwide as of 1st June 2020 and caused a global medical emergency. Healthcare professionals have been struggling to devise appropriate therapeutic strategies against the virus mainly due to the diverse range of symptoms and multiple-organ failure in infected patients. Several broad-spectrum antiviral drugs are being used for treatment; however, there is yet no specific drug or vaccine against the virus. Multiple-organ failure due to hyperactivity of the immune system resulting in cytokine storms is a major reason for death among the 5% critically ill patients. In this article, we have discussed the damage caused by COVID-19 on different organs of the human body.